LEGAL FOUNDATIONS FOR ENSURING OCCUPATIONAL HEALTH IN UKRAINE - Firsova O. D.; Solomenna L. V. (Pressing Problems of Public Administration, 2021)
Under the EU-Ukraine Association Agreement, Ukraine is required to ensure safe and healthy working conditions in order to comply with the European standards of a decent working environment. The country is constantly improving the legal framework for the prevention of occupational accidents and diseases, as well as mitigation of risk factors behind their development. Notably, Ukraine has already ratified seventy-one conventions of the International Labour Organization, including the eight fundamental conventions, the four governance (priority) conventions and fifty-nine of the 177 technical conventions. Nevertheless, the existing system of occupational safety and health does not correspond to the present socio-economic context and shows signs of certain disproportion regarding the actual needs of citizens and businesses. The national law distinguishes between “labour protection”, which is responsible for industrial safety, and “labour hygiene”, which oversees hygiene, sanitation and work environment. The analysis of the legal framework on occupational health indicates that this goes contrary to more holistic approaches typically applied internationally. For this reason, it is pertinent for Ukraine to establish a corresponding system with a “proactive” stance on preventive measures, as well as to change the object of public policy, shifting it away from “labour protection/hygiene” to “occupational safety and health” (OSH). As the first step in this direction, the government has already approved the Concept of the reforming of the National OSH management system. The Concept envisions a set of reforms leading towards safer and healthier working conditions, and minimization of the negative impact of socio-economic consequences of work on human health and productivity. The successful compliance of national legislation with the international norms, notably the EU directives, require several additional pre-conditions. This includes the development of the National strategy for the promotion of occupational safety and health and the enactment of a specific law, which would serve as a legal foundation for the national system of professional hazard prevention and define the main functions, duties and rights of all the parties involved in occupational safety and health (public authorities, employees, employers).